Asthma: Differential Diagnosis and Comorbidities - Ullmann, Nicola; Mirra, Virginia; Di Marco, Antonio; Pavone, Martino; Porcaro, Federica; Negro, Valentina; Onofri, Alessandro; Cutrera, Renato (Frontiers in Pediatrics, 2018)
Childhood asthma remains a multifactorial disease with heterogeneous clinical phenotype and complex genetic inheritance. The primary aim of asthma management is to achieve control of symptoms, in order to reduce the risk of future exacerbations and progressive loss of lung function, which results especially challenging in patients with difficult asthma. When asthma does not respond to maintenance treatment, firstly, the correct diagnosis needs to be confirmed and other diagnosis - such as cystic fibrosis, primary ciliary dyskinesia, immunodeficiency conditions or airway and vascular malformations - need to be excluded. If control remains poor after diagnostic confirmation, detailed assessments of the reasons for asthma being difficult-to-control are needed. Moreover, all possible risk factors or comorbidities (gastroesophageal reflux, rhinosinusitis, dysfunctional breathing and/or vocal cord dysfunction, obstructive sleep apnea and obesity) should be investigated. At the same time, the possible reasons for poor symptom control need to be find in all modifiable factors which need to be carefully assessed. Non-adherence to medication or inadequate inhalation technique, persistent environmental exposures and psychosocial factors are, currently, recognized as the more common modifiable factors. Based on these premises, investigation and management of asthma require specialist multidisciplinary expertise and a systematic approach to characterising patients' asthma phenotypes and delivering individualised care. Moreover, since early wheezers are at higher risk of developing asthma, we speculate that precocious interventions aimed at early diagnosis and prevention of modifiable factors might affect the age at onset of wheezing, reduce the prevalence of persistent later asthma and determine long term benefits for lung health.